Traditional detoxification of wild yam (Dioscorea hispida Dennst) tuber in chips processing at East Java, Indonesia - Teti Estiasih; Kgs. Ahmadi; Irawati Nur Indah Sari; Dessy Eka Kuliahsari; Erryana Martati (Journal of Ethnic Foods, 2022)
Abstract Dioscoreaceae or yam is a family of tuber that comprises many members with variability in utilization and their intensity of consumption. This family has wide variability and is used not only as food but also for medical purposes due to their bioactive compounds. One of the Dioscoreaceae family is wild yam (Dioscorea hispida Dennst), rich in carbohydrates but has an obstacle of high cyanide level. Historically, along with cassava, wild yam is the staple food in some places in Indonesia. There is a long history of traditional detoxification methods of wild yam with slightly different steps among different places. The shifting of staple food to rice excludes wild yam consumption. One of the remaining products from wild yam is chips. Wild yam chips are a traditional snack that is also produced by traditional detoxification. This paper is aimed to review the scientific basis for each step in traditional wild yam chips processing to remove cyanogenic compounds. This review was based on the observations of traditional wild yam tuber chip processing and unstructured interview with the wild yam tuber chip maker at 6 locations in East Java, Indonesia. Relevant literature was used to explain the scientific basis of the detoxification methods based on the definite inclusion and exclusion criteria. Also, the variability of processing methods was compared among different locations. In general, the steps of traditional detoxification during wild yam tuber chips processing are slicing the peeled wild yam tubers, mixing with the rubbing ash, pressing, drying, soaking, boiling/steaming, and sun drying. Slicing, rubbing, and pressing in chips processing is aimed to convert cyanogenic glycoside into acetone cyanohydrin. The alkaline pH due to ash rubbing makes spontaneous decomposition of acetone cyanohydrin into HCN. HCN is easily removed by dissolution and heating (drying and steaming/boiling). Thermal treatment also spontaneously decomposes cyanohydrin into free HCN. All of the cyanogenic compounds are water-soluble which soaking and washing are aimed to remove all compounds. Consecutive, complicated, and time-consuming processing completely removes cyanogenic compounds and produces safe wild yam tuber chips. The key finding of this review is the purpose of every step in wild yam tuber detoxification has a scientific basis to reduce cyanogenic compounds gradually. This process produces a very low cyanide level in the final product. In conclusion, traditional detoxication reduces cyanogenic compounds to a safe level.